Silence Behind Green Sukuk: Stakeholder Voices on the Effectiveness and Resilience of Sharia Financial Institutions in Green Financing: Keheningan di Balik Sukuk Hijau: Suara Pemangku Kepentingan tentang Efektivitas dan Ketahanan Lembaga Keuangan Syariah dalam Pembiayaan Hijau - Abdi Dzul Jalal Ikram; A.M. Nur Atma Amir; Achmad Riady; Jamaluddin Majid (Program Studi Akuntansi Lembaga Keuangan Syariah, Politeknik Wahdah Islamiyah Makassar, 2025)
This study examines green sukuk as a reflection of the interconnectedness between spirituality, economics, and sustainability in Indonesia’s Islamic finance. Employing a descriptive qualitative method and a reflective literature review, it explores the often-overlooked spiritual dimension behind the success narrative of green sukuk, particularly the absence of maqāṣid al-syarīʿah (the higher objectives of Islamic law) in both policy formulation and public perception. The findings indicate that sustainability in Islam extends beyond environmental aspects to include spiritual, ethical, and moral dimensions. By framing green sukuk as a form of “structural da‘wah,” this research highlights its potential to harmonize divine values with contemporary financial practices. Ultimately, the study proposes a maqāṣid-based green finance framework that emphasizes holistic sustainability, integrating faith-based principles with sustainable development goals to strengthen the ethical foundation of Islamic financial instruments in Indonesia.